2x+23=-3x-12

Simple and best practice solution for 2x+23=-3x-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+23=-3x-12 equation:



2x+23=-3x-12
We move all terms to the left:
2x+23-(-3x-12)=0
We get rid of parentheses
2x+3x+12+23=0
We add all the numbers together, and all the variables
5x+35=0
We move all terms containing x to the left, all other terms to the right
5x=-35
x=-35/5
x=-7

See similar equations:

| 3=3x=-6 | | C=$37.00+0.45n | | 8-3x-10=20 | | 2(x+5)+25+x=51 | | 4(w+6=) | | 2/26=1/x | | y/2+22=88 | | 3x-5=-48-40x* | | -1=(5+x/)6 | | -6=-8+x/10 | | -7d-4d+2d=40 | | m-38=20 | | 2x+3=2x7 | | y=100(1.06)^12 | | 36=9s | | -w+10=9w | | 4^x+3+3=46 | | m+15=75 | | 4x+2(x-6)=96 | | -15(x-6)=-66 | | 5r-15=35 | | 3x-10+x= | | q+21=60 | | 9x2=8x2 | | 2(91-3x)=5x+61 | | 3=15+n | | –w+10=9w | | c–8=179 | | f-9=66 | | 4r-6=46 | | 2(c-4)=98 | | 34(4x-8)=2x+2 |

Equations solver categories